Comparison of Canal Transportation, Separation Rate, and Preparation Time between One Shape and Neoniti (Neolix): An In Vitro CBCT Study - Maryam Kuzekanani; Faranak Sadeghi; Nima Hatami; Maryam Rad; Mansoureh Darijani; Laurence James Walsh (International Journal of Dentistry)
Purpose. This in vitro study compared root canal preparation in curved mesiobuccal canals of molar teeth using either the One Shape™ or the Neoniti (Neolix) rotary NiTi single-file systems, assessing canal transportation, instrument separation and time required for preparation. Methods. Extracted maxillary and mandibular human molar teeth with mesiobuccal canals having apical angles of curvature between 25 and 35o were selected and embedded in acrylic resin blocks, and an initial CBCT was taken. The teeth were divided into two equal groups (n = 20), and the canals were cleaned and shaped using either Neoniti™ or One Shape™ engine-driven NiTi rotary files. Each individual instrument was used to prepare 5 canals. The time required for the preparation of each canal was recorded. Postpreparation CBCT scans were taken and used to determine the extent of canal transportation at levels of 2, 4, 6, and 8 mm from the apex. The Kolmogorov–Smirnov test for normality was applied, and then, datasets were compared using independent t-tests, with a threshold of P<0.05. Results. Neoniti rotary files caused significantly less canal transportation of the curved canals (P=0.0001). On the other hand, the time required for canal preparation was significantly shorter for One Shape (P=0.0001). No instrument separation was recorded in both groups. Conclusion. Based on these results, the Neoniti™ rotary file system is preferred because it maintains the original shape of curved root canals better than One Shape™; even though this benefit comes at the cost of an increase in preparation time in clinical practice, the better technical performance may be more important than a difference in procedural time.